2011
DOI: 10.1037/a0022066
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among client–therapist personality congruence, working alliance, and therapeutic outcome.

Abstract: Despite the importance of the working alliance in therapeutic outcome, little is known about the factors associated with its formation. We advance that personality similarity between client and therapist is one such factor pertinent to the working alliance. In this study, personality similarity in 32 client-therapist dyads was examined for its relations to the bond, task, and goal elements of the working alliance (Bordin, 1979, Psychotherapy: Theory, Research, and Practice, 16, 252-260) and therapeutic outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 20 publications
0
32
1
Order By: Relevance
“…Second, some variables included in this review have not yet been adequately studied. For example, most clinicians would endorse the view that the therapist's personality can play a significant role in therapy outcome (Arthur, ; Taber et al, ). Finally, it is critical that we do not lose sight of the equally important contribution of the patient in developing the therapeutic relationship and achieving better therapeutic outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, some variables included in this review have not yet been adequately studied. For example, most clinicians would endorse the view that the therapist's personality can play a significant role in therapy outcome (Arthur, ; Taber et al, ). Finally, it is critical that we do not lose sight of the equally important contribution of the patient in developing the therapeutic relationship and achieving better therapeutic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Schaffer (1982) have not yet been adequately studied. For example, most clinicians would endorse the view that the therapist 0 s personality can play a significant role in therapy outcome (Arthur, 2001;Taber et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These inter-disorder differences highlight the complexities inherent in attempting to link specific pathologies to the working alliance. Additionally, research has demonstrated that personality similarity between patient and therapist may be an important factor, with more similar personalities resulting in a stronger working alliance (Taber, Leibert, & Agaskar, 2011).…”
Section: Alliance: Not the Whole Storymentioning
confidence: 99%
“…Such choices and attitudes can change not only in the course of training but even more importantly, in the course of professional life. The fit between the personalities of the patient and the therapist (Taber et al, 2011) and other topics like the patient’s symptom severity on outcome and alliance (Dinger et al, 2016) have been investigated. In the most recent decades the relationship between therapists’ personality characteristics, working alliance and outcome of psychotherapy also has been studied and reviewed (Ackerman and Hilsenroth, 2001, 2003; Orlinsky et al, 2004; Norcross and Wampold, 2011).…”
Section: Introductionmentioning
confidence: 99%